Eastern Caribbean Currency Union : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper analyzes the income dispersion and comovement in the Eastern Caribbean Currency Union region. It finds that incomes are diverging, with the Leeward Islands converging to a higher income level than the Windward Islands. The paper examines the macroeconomic impact of trade preference erosion on the Windward Islands and demonstrates the substantial impact from preference erosion on growth, trade balances, and fiscal positions. The paper also analyzes the size of the informal economy in the Caribbean.